Towards an extended BPMS prototype: Open challenges of BPM to flexible and robust orchestrate of uncertain processes - Saraeian, Shideh; Shirazi, Babak; Motameni, Homayun (Computer standards and interfaces, 2018)
•Propose an extended BPMS prototype to flexible and robust orchestrate of uncertain processes.•The uncertain BPMS engine design are based on component and layer-oriented architecture style.•Operating new designed engine beside classic BPMSs engines through CORBA standard.•Flexibility and robustness of the extended BPMS using well-defined interfaces. Nowadays, uncertainty is widely discussed as serious a challenge against business decision-making. The current business process management systems (BPMSs) are only able to manage certain processes, where there is practically a huge gap between what is expected and what is realized due to uncertainty. This study developed an extended BPMS prototype to facilitate and improve any business process management subject to uncertainty. This prototype can model, design, control and optimize in uncertainty modes, in addition to classic BPMSs operations. For developing a new prototype, the authors first provided a meta-model for designing new engine functions. Thereafter, by defining the architecture style and abstract model, defining user interfaces and component interfaces, uncertain BPMS prototype with CORBA standards created. Furthermore, flexible components are implemented to deal with uncertainty during run-time. This paper has used three evaluation methods to validate the proposed uncertain BPMS prototype. Firstly, an executable prototype has been built and evaluated with a rating model, which obtains quantitative metrics. The comparison between the proposed uncertain BPMS prototype and other classic BPMSs has effectively demonstrated the ability of an extended BPMS prototype in BP management under uncertainty modes. Secondly, a case study in oil and gas industry was studied with a focus on the industry 4.0. The results have revealed the improvement in planning service time after using the proposed prototype. Thirdly, the efficiency of uncertain BPMS prototype has been investigated through different object-oriented software metrics. These results also show the ability of the extended BPMS prototype to flexibly and robustly orchestrate uncertain processes.